2013
DOI: 10.1155/2013/561692
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Dysgraphia in Primary Progressive Aphasia Compared to Post-Stroke Aphasia

Abstract: Abstract. We report patterns of dysgraphia in participants with primary progressive aphasia that can be explained by assuming disruption of one or more cognitive processes or representations in the complex process of spelling. These patterns are compared to those described in participants with focal lesions (stroke). Using structural imaging techniques, we found that damage to the left extrasylvian regions, including the uncinate, inferior fronto-occipital fasciculus, and sagittal stratum (including geniculost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…A recent study from our laboratory has identified early spelling patterns that predict the variant of PPA into which the patient is like-ly to evolve, when only naming and spelling are affected (such that the patient does not yet meet criteria for any one variant). Our study further determined which cognitive processes underlying spelling are affected in each of the PPA variants [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from our laboratory has identified early spelling patterns that predict the variant of PPA into which the patient is like-ly to evolve, when only naming and spelling are affected (such that the patient does not yet meet criteria for any one variant). Our study further determined which cognitive processes underlying spelling are affected in each of the PPA variants [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have recently focused great effort on the development of interventions to reduce the rate of decline. Spelling is often one of the earliest affected language skills (Faria et al, 2013; Mesulam, 2001; Sepelyak et al, 2011), and, given today's extensive use of email and texting technologies, may cause particular concern. Language interventions targeting the main cognitive mechanisms recruited during spelling have been modest but encouraging in PPA (Rapp & Glucroft, 2009; Tsapkini & Hillis, 2013).…”
mentioning
confidence: 99%
“…According to Faria et al (2013), patients with lvPPA usually present with phonological dysgraphia, characterized by an impaired phonology-to-orthography conversion route and partially impaired access to orthographic word forms. According to Faria et al (2013), patients with lvPPA usually present with phonological dysgraphia, characterized by an impaired phonology-to-orthography conversion route and partially impaired access to orthographic word forms.…”
Section: C Sentence Repetition In a Patient With Lvppamentioning
confidence: 99%